2017
DOI: 10.1038/ncomms14112
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid generation of hypomorphic mutations

Abstract: Hypomorphic mutations are a valuable tool for both genetic analysis of gene function and for synthetic biology applications. However, current methods to generate hypomorphic mutations are limited to a specific organism, change gene expression unpredictably, or depend on changes in spatial-temporal expression of the targeted gene. Here we present a simple and predictable method to generate hypomorphic mutations in model organisms by targeting translation elongation. Adding consecutive adenosine nucleotides, so-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…As expected, we observed robust changes in mRNA levels ( Figure 3A) and substantial losses in protein expression ( Fig. 3B) for reporters with polyA tracks in both neonatal human dermal fibroblasts (HDFs) and AT-genome rich T. thermophila (10,11). We observed minimal, if any effects, of polyA track insertion on reporter mRNA and protein expression in P. falciparum (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, we observed robust changes in mRNA levels ( Figure 3A) and substantial losses in protein expression ( Fig. 3B) for reporters with polyA tracks in both neonatal human dermal fibroblasts (HDFs) and AT-genome rich T. thermophila (10,11). We observed minimal, if any effects, of polyA track insertion on reporter mRNA and protein expression in P. falciparum (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Recently, it was demonstrated that the translation of genes with polyadenosine runs (polyA tracks), primarily coding for lysine residues, is attenuated in the majority of tested eukaryotic and prokaryotic organisms due to ribosomal stalling and frameshifting on such RNA motifs (8)(9)(10)(11)(12)(13)(14)(15). In humans, the presence of just 12 adenosines in an mRNA coding region will deplete the protein synthesis of a given gene by more than 40% (9,10). The consequence of translational arrest is activation of one or more mRNA surveillance mechanisms and has been demonstrated in studies of human, yeast and E. coli (9,12).…”
Section: Mainmentioning
confidence: 99%
“…In this context, rather than slowing elongation, the reduced mRNA structure caused by AT-rich nonoptimal codons is suggested to enhance the rate of translation and increase translation efficiency, possibly by optimizing the spacing between ribosomes (40). Yet, these nonoptimal codons might also impact the efficiency of translation initiation, as including more than eight consecutive nonoptimal codons in the 5Ј end of coding sequences causes decreased protein expression (91,92).…”
Section: Ribosome Stalling Dictates Gene Expressionmentioning
confidence: 99%
“…Subsequently, to test whether RhoGAPp190 mRNA upregulation can contribute to the locomotor dysfunction observed in the tbph-null flies, we assayed the genetic interaction between RhoGAPp190 and tbph by examining the consequences of the combined RhoGAPp190 / tbph silencing on climbing ability. Since flies bearing homozygous tbph-null mutations show limited larval lethality [ 15 18 ], tbph hypomorphic flies (carrying a milder phenotype) [ 19 22 ] were used to test the genetic interaction between this nuclear factor and RhoGAPp190. Two different RhoGAPp190 RNAi fly lines (namely, 6429 and 6430), generated by expressing RhoGAPp190 and tbph RNAi in tbph hypomorphic flies, were used for this experiment.…”
Section: Resultsmentioning
confidence: 99%